Training load--injury paradox: is greater preseason participation associated with lower in-season injury risk in elite rugby league players?. Issue 8 (13th April 2016) - Windt, Johann; Gabbett, Tim J; Ferris, Daniel; Khan, Karim M
Abstract : Aim: To determine whether players who completed a greater number of planned preseason training sessions were more or less likely to be injured during the competitive season. Methods: A cohort of 30 elite rugby league players was prospectively studied during their 17-week preseason and 26-round competitive season. Injuries were recorded using a match time loss definition. Preseason participation was quantified as the number of 'full' training sessions that players completed, excluding modified, rehabilitation or missed sessions. In-season training load variables, collected using global positioning system (GPS) data, included distance covered (m), high-speed distance covered (m) and the percentage of distance covered at high speeds (%). Multilevel logistic regression models were used to determine injury likelihood in the current and subsequent week, with random intercepts for each player. Odds ratios (OR) were used as effect size measures to determine the changes in injury likelihood with (1) a 10-session increase in preseason training participation or (2) standardised changes in training load variables. Results: Controlling for training load in a given week, completing 10 additional preseason sessions was associated with a 17% reduction in the odds of injury in the subsequent week (OR=0.83, 95% CI=0.70 to 0.99). Increased preseason participation was associated with a lower percentage of games missed due to injury (r=−0.40, p<0.05), with 10 preseason sessions predicting a 5% reduction in the percentage of games missed. Conclusions: Maximising participation in preseason training may protect elite rugby league players against in-season injury.